2004
DOI: 10.1016/j.ccr.2004.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CXCR4 is essential for HER2-mediated tumor metastasis

Abstract: The receptor tyrosine kinase HER2 enhances tumor metastasis; however, its role in homing to metastatic organs is poorly understood. The chemokine receptor CXCR4 has recently been shown to mediate the movement of malignant cancer cells to specific organs. Here, we show that HER2 enhances the expression of CXCR4, which is required for HER2-mediated invasion in vitro and lung metastasis in vivo. HER2 also inhibits ligand-induced CXCR4 degradation. Finally, a significant correlation between HER2 and CXCR4 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
454
9
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(492 citation statements)
references
References 45 publications
22
454
9
7
Order By: Relevance
“…The relationship between HER2 overexpression and hematogenous (liver) metastases is unknown at the present. Li et al [24] reported that HER2 overexpression mediates a chemokine receptor, CXCR4- associated metastases. Therefore, we speculate that HER2 overexpression involves or promotes liver metastases, but not peritoneal and lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between HER2 overexpression and hematogenous (liver) metastases is unknown at the present. Li et al [24] reported that HER2 overexpression mediates a chemokine receptor, CXCR4- associated metastases. Therefore, we speculate that HER2 overexpression involves or promotes liver metastases, but not peritoneal and lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…However, HER2-positive tumors may also have a specific predilection to central nervous system (CNS). Indeed, some studies demonstrated that CNS environment may facilitate migration and settling of HER2-positive cells [27,28]. Recently, overexpression of HER2 has been found to increase the colonization of breast cancer cells in the brain in vivo [29].…”
Section: Discussionmentioning
confidence: 99%
“…45,48 High-level expression of CXCR4 on neoplastic cells is associated with relatively poor overall survival in patients with breast cancer. 127 The multiple tumor-promoting effects of CXCL12 in breast cancer suggest that CXCR4 antagonists alone or in combination with cytotoxic drugs could decrease the rate of recurrence in the adjuvant setting where patients are likely to have MRD, and/or increase the response rates to conventional therapy in advanced stages of the disease. Animal breast cancer models using T140 73 and Plerixafor 128 have shown promising results, suggesting that CXCR4 antagonists should be explored in this cancer.…”
Section: Cxcr4 In Breast Cancermentioning
confidence: 99%